The employment of vaccinia virus for colorectal cancer treatment: A review of preclinical and clinical studies - Qiaoyun Ling; Bichun Zheng; Xudong Chen; Shaoshun Ye; Quan Cheng (Taylor & Francis Group, 2022)
Colorectal cancer (CRC) is one of the leading malignancies that causes death worldwide. Cancer vaccines and oncolytic immunotherapy bring new hope for patients with advanced CRC. The capability of vaccinia virus (VV) in carrying foreign genes as antigens or immunostimulatory factors has been demonstrated in animal models. VV of Wyeth, Western Reserve, Lister, Tian Tan, and Copenhagen strains have been engineered for the induction of antitumor response in multiple cancers. This paper summarized the preclinical and clinical application and development of VV serving as cancer vaccines and oncolytic vectors in CRC treatment. Additionally, the remaining challenges and future direction are also discussed.